Immune Thrombocytopenic Purpura Detected with Oral Hemorrhage: a Case Report - Tsutomu Sugiura; Kazuhiko Yamamoto; Kazuhiro Murakami; Satoshi Horita; Yumiko Matsusue; Chie Nakashima; Tadaaki Kirita (Shiraz University of Medical Sciences, 2018)
Immune thrombocytopenic purpura (ITP) is an immune-mediated acquired disease found in both adults and children. It is characterized by transient or persistent decreases in the platelet count. We report a case of ITP detected based on oral hemorrhagic symptoms. The patient was a 79-year-old female with no significant past medical history. She presented with sudden onset of gingival bleeding and hemorrhagic bullae on the buccal mucosa. Gingival bleeding was difficult to control. Laboratory tests revealed severe thrombocytopenia with a platelet count as low as 2000/μL. Under a provisional diagnosis of a hematological disorder, she was referred to a hematologist. A peripheral smear showed normal-sized platelets. A bone marrow examination revealed increased numbers of megakaryocytes without morphologic abnormalities. The patient was diagnosed with ITP and treated with a combination of pulsed steroid therapy and high-dose immunoglobulin therapy. However, her severe thrombocytopenia was refractory to these treatments. Then, a thrombopoietin receptor agonist was begun as a second-line treatment. Her platelets rapidly increased, and no bleeding complications were reported. Because oral symptoms can be one of the initial manifestations of ITP, dentists should be familiar with the clinical appearance of ITP, and attention must be paid to detect and diagnose unidentified cases.